KORUPSI POLITIK DAN PELANGGARAN HAK ASASI MANUSIA DI INDONESIA - Lestari, Yeni Sri; Chadijah, Devi Intan; Sariyanti, Lilis (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
The number of political elites who hold positions both in parliamentary institutions and regional heads and ministers has influenced the increase in the number of political corruption in Indonesia. However, until now there has been no regulation that is able to reduce the number of political corruption, both to corruptors and to improve the legal system. One of the impacts of the increasing political corruption in Indonesia is expanding human rights violations. The purpose of this study is to describe the impact of political corruption on human rights violations. This study uses descriptive qualitative research method through literature study. The results found that political corruption leads to misappropriation of the country's economy, a tyrannical system of government, the increasing practice of collusion between rulers and businessmen, the bluntness of laws and regulations and the death of the country's democracy.